2015
DOI: 10.5423/ppj.oa.01.2015.0001
|View full text |Cite
|
Sign up to set email alerts
|

Construction of a High-Quality Yeast Two-Hybrid Library and Its Application in Identification of Interacting Proteins with Brn1 in Curvularia lunata

Abstract: Curvularia lunata is an important maize foliar fungal pathogen that distributes widely in maize growing area in China, and several key pathogenic factors have been isolated. An yeast two-hybrid (Y2H) library is a very useful platform to further unravel novel pathogenic factors in C. lunata. To construct a high-quality full length-expression cDNA library from the C. lunata for application to pathogenesis-related protein-protein interaction screening, total RNA was extracted. The SMART (Switching Mechanism At 5′… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
9
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…In order to explore the biology of a plant response mechanism—genes such as those responsible for survival, dehydration avoidance, and development—a full-length cDNA library was constructed using wheat leaves from a drought condition. The high-quality-expression cDNA library can offer molecular resources for the analysis of genes involved in biology and for studying its protein function [ 41 ]. Our library storage was 5.30 × 10 5 cfu/mL, and the titer was 3.62 × 10 7 cfu/mL.…”
Section: Discussionmentioning
confidence: 99%
“…In order to explore the biology of a plant response mechanism—genes such as those responsible for survival, dehydration avoidance, and development—a full-length cDNA library was constructed using wheat leaves from a drought condition. The high-quality-expression cDNA library can offer molecular resources for the analysis of genes involved in biology and for studying its protein function [ 41 ]. Our library storage was 5.30 × 10 5 cfu/mL, and the titer was 3.62 × 10 7 cfu/mL.…”
Section: Discussionmentioning
confidence: 99%
“…To uncover the pathogenicity mechanisms of CLS, most researches have focused on identifying virulence factors, such as melanin ( Gao et al, 2012 , 2015b ), and toxin ( Gao et al, 2014a ; Liu et al, 2009 ). Fungal melanins, formed by the oxidative polymerisation of phenolic compounds, are essential for enhance the mechanical strength of the infection into the host plant epidermis and contribute to virulence in numerous types of plant diseases ( Gao et al, 2015e ). Previous studies have also indicated that the albino C. lunata strains present in wild-type (WT) strains are weakly virulent to maize leaves, supporting the conclusion that melanin is a crucial virulence factor for C. lunata in susceptible maize leaves ( Yan et al, 2005 ).…”
mentioning
confidence: 99%
“…A high-quality Y2H library can provide molecular resources to analyze protein functions and interactions based on a known protein to facilitate the construction of protein networks 19 . These proteins provide baseline information for further elucidating their regulatory network in the development process.…”
Section: Discussionmentioning
confidence: 99%